Ice growth in the greenhouse: A seductive paradox but unrealistic scenario - Weaver, Andrew; Hillaire-Marcel, Claude (Geoscience Canada, 2004)
ABSTRACT The recent IPCC (2001) assessment stated that "Most models show weakening of the Northern Hemisphere Thermohaline Circulation (THC), which contributes to a reduction of surface warming in the northern North Atlantic. Even in models where the THC weakens, there is still a warming over Europe due to increased greenhouse gases." However, there is still a widespread misunderstanding of the possible consequence of climate change on the Atlantic Ocean Meridional Overturning. In particular, it is often touted, especially in the media, that a possible consequence of anthropogenic greenhouse gas emissions is: "the onset of the next ice age". Here we document the history of this misconception and quantitatively show how it is impossible for an ice age to ensue as a consequence of global warming. Through analysis of the paleoclimate record as well as a number of climate model simulations, we also suggest that it is very unlikely that the Atlantic Meridional Overturning will cease to be active in the near future. We further suggest that a region where intermediate water formation may shut down is in the Labrador Sea, although this has more minor consequences for climate than if deep water formation in the Nordic Seas were to cease.